Differences in the Effectiveness of SRQ (Self Reporting Questionnaire) and HRQLQ (Health-Related Quality of Life Questionnaire) with Malamoi Dialect for Early Detection of Mental Disorders Symptoms in Aimas District Residents of Sorong District in 2019 - Butet Agustarika; Panel Situmorang (Journal of Global Pharma Technology, 2020)
Early detection tools for mental disorders can be one of the tools to overcome mental health problems in Indonesia, where there are still many patients with mental disorders who gets an incorrect diagnosis. This study aims to obtain the results of the analysis of differences in the effectiveness of the SRQ and HRQLQ questionnaires in the Aimas District residents of Sorong regency, with the characteristics of the respondents for each questionnaire respectively most are lazy (57.5% and 70%), with elementary school education (50% and 40%) and have jobs as laborers/farmers/fishermen (62.5%). Based on the result of data analysis correlation of Detection of Mental Disorders Symptoms with Question Type, it was concluded that there was a significant difference between the detection of mental disorders using the SRQ and HRQLQ questionnaires, with SRQ effectiveness levels higher than HRQLQ (SRQ's mean rank is 47.50 and HRQLQ at 33.50). Keywords: Self-reporting Questionnaire, Health-related Quality of Life Questionnaire, Mental Health, Malamoi Dialect.